Examination of fecal electrolyte on pediatric patient with intestinal stoma - Haliza, Wilda; Ranuh, Reza Gunadi; Athiyyah, Alpha Fardah; Novi, Theresia; Darma, Andy; Sumitro, Khadijah Rizky; Sudarmo, Subijanto Marto (Edelweiss Applied Science and Technology, 2024)
Intestinal stomas are increasingly performed in pediatric patients to manage various gastrointestinal conditions, such as congenital malformation of intestinal, necrotizing enterocolitis and intestinal obstruction, which are frequently occured in developing countries with Low-Middle Income Country (LMIC). However, the presence of a stoma has possibility of morbidity such as can significantly affect the body’s fluid and electrolyte balance, particularly in infant and under five years old children. This risk is increased due to the immature renal system in pediatric patients, increased loss of fluids and electrolytes through stoma output, especially small intestinal stoma. In addition to being a challenge in the management of infants and children with stomas and intestinal resections, electrolyte imbalances are one of the factors contributing to morbidity and mortality in these group. Early detection of abnormalities can guide timely interventions such as fluid replacement therapy and dietary modifications, prevent complications like dehydration, metabolic acidosis or electrolyte disturbances. Measuring fecal electrolyte provide valuable insights into the patient’s hydration status and potential electrolyte imbalances. Since the fecal sample measuring is the simplest, harmless and noninvasive than the other electrolyte tests, so it can be considered for pediatric patients.